Tongue position assessment during oral phase deglutition in children with anterior open bite and normal vertical overbite - Paula Gonzalez; María Beatriz Martínez; Valentina Sierra; Zulma Vanessa Rueda; Paola Botero-Mariaca (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2019)
Introduction: Tongue position during deglutition presents great variability and can be assessed clinically or with different techniques. Aim: This study aims to determine tongue position during deglutition in children aged 8–16 years with anterior open bite (AOB) and normal vertical overbite (NVO) using a fluorescein technique. Settings and Design: A cross-sectional analytical study was conducted to assess tongue contact points during the oral phase of deglutition. Subjects and Methods: A total of 132 children with AOB and 132 children with NVO were included in this study. The difference between tongue contacts in both groups was performed, and the association between tongue position and anterior occlusion was establish. Statistical Analysis Used: Normal distribution analysis, Parson's Chi-square test (P < 0.05). Results: In AOB, about 28.8% showed tongue contact on the palatal surface of the incisors during the oral phase, 25.8% at the gingival margin, and 22% on the palatal rugae. Regarding NVO, 53% showed contact on the palatal rugae, 28.8% at the gingival margin, and 13.6% at the palatal surface. Conclusion: AOB group presented a higher prevalence of impaired tongue positions compared to NVO controls. The palatal surface was the most frequent contact point in the AOB, whereas tongue showed contact points at the palatal rugae in NVO.